EFEKTIVITAS LUDO WORD GAME (LWG) SEBAGAI MEDIA CHEMO-EDUTAINMENT UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI IKATAN KIMIA DI KELAS X SMAN 16 PADANG - Marni, Niken Gustia (RC-INSTITUT, 2019)
This research aims to reveal the effectivity of ludo word game as chemo-edutainment media to improve student learning outcomes in chemical bonding class 10th at SMAN 16 Padang. The type of this research is a quasi-experimental with a non-equivalent control group design. The population of this research is class 10 MIA from SMAN 16 Padang. The sample of the research was taken by using purposive sampling technique. the chosen sample was class X MIA 1 as experiment class and class X MIA 3 as control class. The instrument was the test learning outcomes, which are the initial test (pretest) and final test (posttest) in the form of 25 objective questions. The result of this research showed that there was difference in learning outcomes between the experiment class and control class. It is proven by posttest average of the experiment class and control class which are 82.6 and 77.3. Data analysis showed that the sample is normally distributed and homogeneous so that t test can be done, earned value t ≥ t1-α is 3.823 > 1.666 so H0 is reject. The data proved that the learning outcomes of experiment class are higher than the learning outcomes of control class. This is also supported by N-Gain value obtained experiment 0.75 with high category and control class 0.67 with medium category.   Keywords: effectivity, ludo word game, chemo-edutainment, chemical bonding, learning outcome